Використання AWS і Heroku для розробки паралельних і розподілених додатків в університетських лабораторіях - Сіциліцин, Юрій Олександрович; Sitsylitsyn, Yurii (Запоріжжя : 2023, 2023)
UA: У цій статті досліджується використання хмарних сервісів, зокрема Amazon Web Services (AWS) і Heroku, для розробки паралельних і розподілених додатків в університетських лабораторіях. Зі зростанням попиту на високопродуктивні обчислення та обробку даних, паралельні та розподілені додатки стали критично важливими для досліджень та освіти в різних галузях. AWS та Heroku надають економічно ефективні та гнучкі рішення для розгортання та управління цими додатками. У статті наведено огляд серверів AWS і Heroku та їхніх переваг для розробки паралельних і розподілених додатків. Вона також описує реалізацію проекту паралельного програмування з використанням серверів AWS і Heroku і порівнює ці дві реалізації з точки зору ціни, масштабованості, простоти використання і співпраці з університетами. Результати цієї статті можуть допомогти дослідникам і викладачам в університетських лабораторіях використовувати хмарні сервіси для своїх потреб у паралельних і розподілених обчисленнях. Результати показують, що і AWS, і Heroku є життєздатними варіантами для розробки і розгортання паралельних і розподілених додатків, з їх власними унікальними перевагами і обмеженнями. EN: This article explores the use of cloud-based services, specifically Amazon Web Services (AWS) and Heroku, for developing parallel and distributed applications in university laboratories. With the increasing demand for high-performance computing and data processing, parallel and distributed applications have become crucial for research and education in various fields. AWS and Heroku provide a cost-effective and flexible solution for deploying and managing these applications. The article provides an overview of AWS and Heroku servers and their benefits for developing parallel and distributed applications. It also describes the implementation of a parallel programming project using both AWS and Heroku servers and compares the two implementations in terms of pricing, scalability, ease of use, and cooperation with universities. The article provided an overview of AWS and Heroku servers, discussed the benefits of using cloud services for parallel and distributed applications, compared the two platforms, and presented a use case demonstrating the implementation of a parallel and distributed application using AWS and Heroku Servers. The paper generated research that can inform researchers and developers of university laboratories about the advantages and limitations of using AWS and Heroku servers for parallel and distributed applications, as well as provide recommendations for using cloud services to achieve efficient data processing and analysis in a laboratory environment. The findings of this article can help researchers and educators in university laboratories to leverage cloud-based services for their parallel and distributed computing needs. The results demonstrate that both AWS and Heroku are viable options for developing and deploying parallel and distributed applications, with their own unique strengths and limitations.
Determination of quantitative indicators for economic analysis of the reliability of cultural equipment
Сіциліцин Ю. О. Використання AWS і Heroku для розробки паралельних і розподілених додатків в університетських лабораторіях. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ, 2023, Вип. 13, том 1. C. 502-515.
Keywords: хмарні сервіси; паралельні і розподілені обчислення; AWS; Heroku; cloud services; parallel and distributed computing